2015
DOI: 10.1007/s11031-015-9491-0
|View full text |Cite
|
Sign up to set email alerts
|

The balance of intrinsic need satisfaction across contexts as a predictor of depressive symptoms in children and adolescents

Abstract: In their Self-Determination Theory (SDT), Deci and Ryan (1985) posit autonomy, competence, and relatedness as three intrinsic needs that contribute to well-being throughout the lifespan. Addressing the argument that the universality with which SDT makes its predictions may ignore critical developmental differences, Ryan and Deci (2000) contend that although these three needs are developmentally persistent, their relative salience may in fact vary across the lifespan. This became apparent with the finding that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 72 publications
3
30
0
Order By: Relevance
“…According to the authors, this difference across age groups might be explained by the increasing importance of peers during adolescence. In some of the analyses on need fulfillment, researchers aggregated across the three needs (e.g., Véronneau et al, 2005), or combined items referring to both peers and teachers to a general relatedness scale (e.g., Emery, Toste, & Heath, 2015;Véronneau et al, 2005). However, in their meta-analysis, van den Broeck et al (2016) concluded that it is inappropriate to compute an average need fulfillment score as each need explained unique variance in the dependent variables and was related differently to diverse outcomes.…”
Section: Research In Children: the Role Of Peers At Schoolmentioning
confidence: 99%
“…According to the authors, this difference across age groups might be explained by the increasing importance of peers during adolescence. In some of the analyses on need fulfillment, researchers aggregated across the three needs (e.g., Véronneau et al, 2005), or combined items referring to both peers and teachers to a general relatedness scale (e.g., Emery, Toste, & Heath, 2015;Véronneau et al, 2005). However, in their meta-analysis, van den Broeck et al (2016) concluded that it is inappropriate to compute an average need fulfillment score as each need explained unique variance in the dependent variables and was related differently to diverse outcomes.…”
Section: Research In Children: the Role Of Peers At Schoolmentioning
confidence: 99%
“…Basic Psychological Needs Theory (BPNT) is an SDT sub-theory which argues that optimal psychological wellbeing requires one to experience a sense of Autonomy, Competence, and Relatedness to maintain one's sense of Self-Determination and in turn one's natural level of intrinsic motivation (Baard et al, 2004;Callens, 2008;Deci et al, 2001;Deci & Ryan, 2000a;DeHaan et al, 2016;Droogenbroeck et al, 2014;Emery et al, 2015;Grouzet et al, 2004;Guay et al, 2003;Martela & Ryan, 2016;Vansteenkiste et al, 2006). There is confirmation of BPNT in the research.…”
Section: Basic Psychological Needs Theory (Bpnt)mentioning
confidence: 67%
“…This curiosity is what Deci and Ryan mean by Intrinsic Motivation. This intrinsic motivation to learn, do, and explore is fragile though. According to SDT, a person must feel that they have sufficient sense of Self-Determination to maintain their natural level of intrinsic motivation for a task (Baard, Deci, & Ryan, 2004;Callens, 2008;Deci et al, 2001; Deci & Ryan, 2000a;DeHaan, Hirai, & Ryan, 2016;Droogenbroeck et al, 2014;Emery, Toste, & Heath, 2015;Grouzet, Vallerand, Thill, & Provencher, 2004;Guay et al, 2003;Vansteenkiste, Lens, & Deci, 2006). This is often described in the literature as somewhat antithetical to the Behaviorist viewpoint in which all actions must be in response to external stimuli (Callens, 2008;Deci & Ryan, 2000b;Deci et al, 1996;Guay et al, 2003;Vansteenkiste et al, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations